Penyuluhan tentang Pentingnya Menjaga Kesehatan Mental Remaja di Pesantren Babussa’adah Al Munawarah di Desa Ulee Tanoh Kecamatan Tanah Pasir Kab Aceh Utara - Srie Wahyuni; Rosalia Putri; Qurananayati Qurananayati; Asmuri Yadna (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Adolescence is a transition phase between childhood and adulthood, there are significant changes in various aspects of life. n addition to physical, psychological and social changes, adolescence is also an important time to develop skills, discover interests, and prepare for adult life The importance of early recognition of forms of mental disorders as an effort to reduce the incidence of mental disorders in society. This activity aims to increase adolescent knowledge through socialization about mental health and its treatment. The target of this Community Service activity is students in pesantren Babussa’addah Al Munawarrah di Desa Ulee Tanoh Kecamatan Tanah pasir, Aceh Utara a total of 30 people and activities take place for one day presenting material using the lecture method followed by evaluation. The results of this community service show an increase in knowledge and students' understanding of mental health causes, symptoms, and treatment. Changes in student understanding by showing greater positive responses. It is hoped that this service will contribute to efforts to maintain mental health and improve the psychological well-being of adolescents.